(untitled) (Journal of Educational Sciences, 2016)
Process of integration of Kazakhstani education in the world education space contributes to support of high status of domestic education and science. In new conditions the modern higher and postgraduate education in the Republic of Kazakhstan is called to provide the country with competitiveness specialists, who are maximally adapted to innovation activity. In the modern world the man as the object and subject of education must possess an ability to orient in difficult situations, predict and make decisions. Analysis of official data shows that the higher education institutions of the country which have multi-profile specialization and diversified strategy, will be able to attract the best graduates and at the expense of self-independence and competent management of resources to provide with competitiveness of higher education institutions on the market of education services. In addition to, the international standards of education require strict definite «places occupation» of the higher education institution by qualified scientific and pedagogical staff.